Analytical Characterization Of Controlled Release Ofloxacin / Carbopol934 Mucoadhesive Polymeric Suspension - SUBHASHREE SAHOO; CHANDRA KANTI CHAKRABORTI; UPENDRA NATH NANDA; SHARMISTHA NAIK; SUBASH CHANDRA MISHRA (International Journal of Pharma and Bio Sciences, 2011)
Mucoadhesive polymeric suspension of Ofloxacin was prepared and optimised with the aim of developing oral controlled release gastro-retentive dosage form. Ofloxacin was standardized by UV Spectroscopic analysis. The qualitative analysis of the formulation was performed by FTIR, XRD and SEM analysis. The results from FTIR study indicated that the mucoadhesive suspension of Ofloxacin showed a very good drug polymer interaction due to esterification and intermolecular hydrogen bonding. The XRD data suggested that the retention of crystalline nature of Ofloxacin in the formulation would lead to increase in stability and drug loading, decrease in solubility and delayed release of the drug from polymeric suspension with better bioavailability and penetration capacity. The SEM image analysis indicated that in the formulation maximum particles were having aspect ratio from 2 to 4 and standard deviation was less, which provided supporting evidences for homogeneous uniformly dispersed stable controlled release formulation of Ofloxacin which was pharmaceutically acceptable.